Vertical Handover Evaluation for Heterogeneous Networks - Ismail, Mohd Taha; Dao, Hassan; Zuhairi, Megat F.; Ghazali, Muhammad Azmin Mohamed (International Journal of Engineering and Technology, 2018)
This study is to simulate a handover in heterogeneous network using MATLAB. The simulation comprises of three different networks that overlap between each other and a UE will be moving across the networks. In mobile telecommunication, mobility management in heterogeneous networks will require a vertical handover in order to utilise different mobile technologies. To achieve a seamless handover between the systems, IEEE 802.21 is set to support algorithm enabling seamless handover in heterogeneous network. Handover failures and unnecessary handoff may be provoked in many situations which is causing a problem in seamless handoff. Thus, the algorithm is tested to minimize handover failures and unnecessary handoff. The controlled environment and a comprehensive analysis that covers the signal strength are evaluated.